UPACARA ADAT PANEN â€œPADI BARU / BIRA MAHIHAWUâ€ MASYARAKAT SUKU MODOLE DI DESA BAILENGIT KECAMATAN KAO BARAT KABUPATEN HALMAHERA UTARA. (Studi Antropologi) - Regel, Hendra; Matheosz, Jenny Nelly; Deeng, Djefry (HOLISTIK, Journal Of Social and Culture, 2019)
These rituals have become a tradition and are part of the daily life of most people because they have been handed down hereditary by their ancestors to the next generation. There are various rituals and traditions to strengthen the existence of the religion adopted by the people; Because of the various traditions related to the life cycle that flourished and became strong when he had been tradition and culture in The Midst of Community Life, where The Essence of his teaching was included In the tradition of society because nobody has no place in community culture.In today's modern era, traditional rice harvesting ceremonies have begun to change. This is because of the strong influence of globalization on the culture of Modole tribe, including in the tradition of new rice harvesting ceremonies. Where, a comparison of the tradition of indigenous rice harvesting ceremonies a new one decade era at the time with this moment is much different. During this time, the tradition of traditional ceremonies was carried out differently from the first; traditionally staged music anddances were rarely performed, starting with modern music.The new rice Harvesting ceremony also has its own meaning in society because through the rice harvesting ceremony as well as an expression of gratitude for the harvest and the abundant blessing will also be created a togetherness, whichTherein there is a sense of caring, respect, giving and loving each other and all this is not detached with the motto of Modole Society namely: O Baliara, o hayanga, o Leleani, o Dora, Deo Hininga which means everyone should be together Care for each other, caring, and loving each other.Â Keywords: ritual, rice, Harvest